Social assistance dynamics in Europe : national and local poverty regimes - Saraceno, Chiara (Policy Press, 2002)
Describing social assistance 'careers' in different national and urban contexts, this innovative book documents the strong interplay between personal biographies and policy patterns - a particularly useful perspective which complements the more structural, top-down approach of much international work in social policy.